The gnu mutation of Drosophila causes inappropriate DNA synthesis in mutant and fertilized eggs. - Freeman, M.; Glover, D.M. (Genes & Development, 1987)
Drosophila melanogaster embryos whose mothers are homozygous for the maternal effect lethal mutation gnu (GNU embryos) under DNA synthesis but no nuclear division; this leads to the formation of a small number of giant nuclei in the syncytial blastoderm. We have shown previously that many components of the mitotic apparatus are present and functional in GNU embryos, and the primary lesion of the gnu mutation has therefore remained obscure. Here, we report that fertilization is not necessary for GNU eggs to develop. Giant nuclei originate from the products of female meiosis, and we see autonomously replicating centrosomes that must be maternally derived. If GNU eggs are inseminated, however, the male pronucleus also undergoes DNA replication. Our observations suggest that the GNU cytoplasm permits DNA synthesis in a relatively unregulated manner. In embryos from females homozygous for gnu and the female sterile haploid mutation mh, we find replication of DNA derived from the male pronucleus. This contrasts with embryos from mothers homozygous for mh alone, in which this does not occur. We propose that the gnu gene product participates in the repression of DNA synthesis found in unfertilized eggs.